Matérias e localidades : identidade e educação - Queiroz, João Paulo, 1966- (2019)
From the hegemonic and post colonizers, discourses, there are proposals of resistance: the contextualization, the local cultural value, the identity. Among the expressions of the various countries the theme is dealt with in some of the 17 articles that we publish in this issue of the journal Matéria-Prima, the 15th.